2011
DOI: 10.1007/s10453-011-9242-y
|View full text |Cite
|
Sign up to set email alerts
|

Airborne bacteria, fungi, and endotoxin levels in residential microenvironments: a case study

Abstract: Limited data are currently available on the concentrations of airborne bacteria, fungi, and endotoxins in indoor environments. The levels of aerial bacteria and fungi were measured at several microenvironments within a well-ventilated residential apartment in Singapore including the living room, kitchen, bedroom, toilet, and at a workplace environment by sampling indoor air onto culture medium plates using the 6-stage Andersen sampler. Total microbial counts were determined by collecting the air samples in wat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
36
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(42 citation statements)
references
References 73 publications
(88 reference statements)
3
36
3
Order By: Relevance
“…However, the observation contrasts with the more transient observation that more spores are aerosolised from many different common indoor fungi at high air velocity if the fungal colonised area is dried out [20,23]. High relative humidity has also been shown as a factor to increase fungal concentrations in other continents and cultures [5,45] were present. This difference was not significant in this study, however.…”
contrasting
confidence: 46%
“…However, the observation contrasts with the more transient observation that more spores are aerosolised from many different common indoor fungi at high air velocity if the fungal colonised area is dried out [20,23]. High relative humidity has also been shown as a factor to increase fungal concentrations in other continents and cultures [5,45] were present. This difference was not significant in this study, however.…”
contrasting
confidence: 46%
“…Previous studies have shown that indoor concentrations of bacteria range from 10 1 to 10 3 colony forming units per m 3 of air with conflicting size distributions (57-59). Our average bacteria concentration of 200 16S gene copies per m 3 air is within the range found in previous research (58, 59). Unlike previous studies, we found that airborne bacteria concentration was relatively uniform throughout all size bins ( S3 Fig ).…”
Section: Discussionsupporting
confidence: 90%
“…All the above species produce harmful secondary metabolites and cause allergic and fungal diseases [42][43][44]. However, qualitative studies of bacteria present in the air at the municipal landfill site in Toru n indicate that Gramnegative bacteria, the source of endotoxins (lipopolysaccharides) as a component of their cell walls constituted only a small percentage (1.8%) of all isolated bacterial strains.…”
Section: Discussionmentioning
confidence: 97%